Fundamental financial accounting concepts - Edmonds, Thomas P. (Boston : McGraw-Hill, 1998)
The book tries to explain how any given business event will affect the income statement, balance sheet, and the statement of cash flows.
Includes index.
rua 25/02/15
Loans
Keywords: Accounting